Infrastructure at crossroads - World Bank (Washington, 2006)
Infrastructure at the Crossroads brings together lessons from the last two decades of World Bank engagement in infrastructure. It analyzes trends in the Bank's infrastructure lending, describes the evolution of the external environment and the Bank's own strategic priorities, and presents lessons about project design and appraisal, poverty focus, private sector participation, environmental and social sustainability, the issue of corruption, and stakeholder communications.
Keywords: Infrastructure (Economics) - Developing countries